Historisch-kritisch edieren: zur Problematik digitaler und analoger Editionsformen - Langkabel, Isabel (Editio, 2024)
The conditions under which historical-critical editions are created depend on technical, scientific and social factors. The emergence of digitality in the humanities in recent decades has contributed to a change in scholarly editing that is not welcomed by all sides. The article therefore uses exemplary editions to examine the supposed contrast between digital and analog editing and attempts to demonstrate that the editorial approach always depends on the subject matter.